IMPLEMENTASI APLIKASI KEPEGAWAIAN CV. LADAPEDAS CREATIVE SURAKARTA BERBASIS WEB - Yunita Yolanda (Fakultas Sains, Teknologi dan Kesehatan Universitas Sahid Surakarta, 2020)
CV. Ladapedas Creative Surakarta is a service company focused on the yearbook. At present, Ladapedas employees have not used the presence and the calculation of employee salaries is manually, namely the company leader calculates the basic salary plus the bonus projects that are carried out by the employee. It makes difficult to get attendance information, discipline and inefficiency in the process of calculating employee salaries. The objectives of this research is to make a Civil Service Application CV. Web-Based Creative Surakarta Ladapedas is expected to accelerate the process of filling employee attendance and the process of calculating employee salaries. Data collection technique used observation, interviews and documentation. The system development method used the waterfall method which consists of four stages namely analysis, design, coding and testing. This application was built using the CodeIgniter framework, the PHP programming language and the MySQL Database while testing using the Webqual method. Based on the concept and design, it can be concluded that the CV staffing application has been built. Ladapedas Creative Surakarta can be accessed by two user namely admin and employee. On the admin page, the are employee data menus, attendance data menus, permit data menus and payroll menus. On the employee page, there is a presence menu, permit menu, view presence menu and salary data menu. The webqual system test result show that the quality of usability, quality of information, quality of interaction simultaneously affect user satisfaction as indicated by the significance value of 0.000<0.05. Therefore, it can be concluded that the user is satisfied with the employement application of CV. Ladapedas Creative Surakarta.